ANALISIS SERAPAN ANGGARAN BELANJA PEMERINTAH KABUPATEN ACEH TENGAH - Ruhmaini Ruhmaini; Syukriy Abdullah; Darwanis Darwanis (Jurnal Perspektif Ekonomi Darussalam (Darussalam Journal of Economic Perspec, 2018)
Local governments have an important role in optimizing local financial management to improve public services to the public. One of the most common financial management issues is the absorption of budget in District Revenue and Expenditure Budgets (APBK) at the end of budget year is often below target or lower than its budget. This will result in the loss of spending benefits because the allocated funds cannot be fully utilized, which means there is iddle money. This study aims to analyze the absorption of budget of the Aceh Tengah District Government based on the type of expenditure, function and its organization. The secondary data obtained from the Qanun of  about the Responsibility and its Implementation of APBK Aceh Tengah for the years 2012-2015 . The results showed that the budget absorption based on the type of expenditure, function and organization fluctuated every year. The average budget absorption from 2012 to 2015 is based on the type of expenditure of 87.03%, the average absorption of expenditure by function of 93.32%, and the average uptake of expenditure by the organization of 94.44%.Pemerintah daerah memiliki peran penting dalam mengoptimalkan pengelolaan keuangan daerah untuk meningkatkan pelayanan publik kepada masyarakat. Salah satu masalah pengelolaan keuangan yang sering ditemui adalah serapan anggaran belanja daerah pada APBK diakhir tahun anggaran seringkali berada dibawah target atau lebih rendah dibandingkan dengan anggarannya. Hal ini akan mengakibatkan hilangnya manfaat belanja karena dana yang dialokasikan ternyata tidak semuanya dapat dimanfaatkan, yang artinya terjadi iddle money. Penelitian ini bertujuan untuk menganalisis serapan anggaran belanja Pemerintah Kabupaten Aceh Tengah berdasarkan jenis belanja, berdasarkan fungsi dan berdasarkan organisasi. Data yang dianalisis terdiri dari data sekunder yang diperoleh dari qanun APBK Aceh Tengah tahun 2012-2015. Hasil penelitian menunjukkan bahwa serapan anggaran belanja bedasarkan jenis belanja, fungsi dan organisasi berfluktuatif setiap tahunnya. Rata-rata serapan anggaran dari tahun 2012 sampai dengan 2015 berdasarkan jenis belanja sebesar 87,03%, rata-rata serapan belanja berdasarkan fungsi sebesar 93,32%, dan rata-rata serapan belanja berdasarkan organisasi sebesar 94,44%.Keywords: budget absorpsion, expenditure type, expenditure function, organization.